In-Operando Anomalous Small-Angle X-Ray Scattering Investigation of Pt3Co Catalyst Degradation in Aqueous and Fuel Cell Environments. Issue 14 (1st January 2015) - Gilbert, James A.; Kropf, A. Jeremy; Kariuki, Nancy N.; DeCrane, Stacy; Wang, Xiaoping; Rasouli, Somaye; Yu, Kang; Ferreira, Paulo J.; Morgan, Dane; Myers, Deborah J.
Abstract : Platinum-cobalt alloy nanoparticles are of great interest as cathode catalysts for PEMFCs as they have been shown to have enhanced activity versus platinum. However, their relative stability against loss of electrochemically-active surface area in relation to Pt catalysts is still debated. In this study, the evolutions of Pt3 Co particle size distributions (PSDs) in fuel cell and aqueous environments were followed during accelerated stress tests (ASTs) using in-operando ASAXS. The measured evolutions showed a degradation mechanism dominated by loss of particles smaller than the critical particle diameter (<5.2 to 6.1 nm, CPD), which depended on environment and the AST. These evolutions were compared to that of a Pt catalyst with a similar initial PSD, which was found to have a lower degradation rate than Pt3 Co. The ASAXS data, as well as data from aqueous dissolution, X-ray absorption spectroscopy, individual particle energy-dispersive spectroscopy, X-ray fluorescence spectrometry, and kinetic Monte Carlo calculations support a loss mechanism of increased Pt dissolution from Pt3 Co versus Pt due to destabilization caused by extensive dealloying of particles <∼5 nm during ASTs.